Dynamic currency linkages between select emerging market economies: An empirical study - Arjun Mittal; Sanjay Sehgal; Anand Mittal (Cogent Economics & Finance, 2019)
In this article, we examine the dynamic currency linkages for BRIS (Brazil, Russia, India and South Africa) and 15 other emerging market economies (EMEs) using weekly data from 2001 to 2018. Using the asymmetric dynamic conditional correlation (ADCC)-EGRARCH framework, we find that the average correlation between BRIS currencies in the pre-crisis period is low and stood at 0.29, which rose to 0.39 in the post-crisis period implying contagion effects. Based on both ADCC results and Diebold-Yilmaz, Vector Autoregressive (VAR)framework enhanced by Greenwood-Nimmo block aggregation technique, we find that Brazil is a net transmitter while Russia, India and South Africa seem to be net receivers of information based on the first two moments. We further find empirical support for expanding BRIS into a larger economic block. Based on prior research findings on equity market linkages on BRICS and EMEs as well as our work on currency market linkages, we suggest Mexico, Poland and Hungary as potential candidates to be included in this economic block in the first phase. Turkey, Chile, Columbia and Romania may be included in the next phase as they dominate BRIS in either stock or currency markets of BRIS. This study is pertinent for global policymakers, international monetary agencies, currency investors and academia.
Keywords: C13; C53; F21; F36; G15; 330; BRICS; EMEs; return spillovers; volatility spillovers; ADCC; Diebold-Yilmazcurrency